Estetika ideologi Media Above the Line produk suplemen merek “Madurasa” PT Air Mancur - Pujiyanto, Pujiyanto (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This study aims to determine the textual and contextual aesthetic ideology in above-the-line Madurasa advertising. This research applied a qualitative descriptive case study design focusing on drawings or written elements in advertisements published in newspapers, tabloids, and magazines. The data were obtained through observation, interviews, and documentation, while the analysis employed Antonio Gramsci’s theory of ideology and hegemony. The results show that advertising media function as ideological strategies of hegemony through elements of typography, images, colors, logos, and layout.